2014
DOI: 10.1080/11250003.2014.984781
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of morphological parameters of bone formation in Sprague–Dawley rats of different ages byin vivofluorochrome labeling

Abstract: Our study focuses on the morphological parameters of bone growth and bone formation in Sprague-Dawley (SD) rats of different ages, using fluorochrome labeling in vivo. We concluded that bone longitudinal growth rate (LGR) and bone mineral apposition rate (MAR) were significantly increased in both the 1-and 3-month-old rats compared with the 6-and 14-monthold rats, and that of the parameters were significantly decreased in both the 6-and 14-month-old rats. Meanwhile, bone formation rate (BFR) and percent labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…) through increased connectivity as observed in our study. Our findings for BV/TV, Tb.Sp, Tb.Th, and Tb.N are in agreement with other studies, where similar patterns also were observed for loaded and normal bone growing process for aged rats and mice bone structure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…) through increased connectivity as observed in our study. Our findings for BV/TV, Tb.Sp, Tb.Th, and Tb.N are in agreement with other studies, where similar patterns also were observed for loaded and normal bone growing process for aged rats and mice bone structure.…”
Section: Discussionsupporting
confidence: 93%
“…(83) Indeed, it has been shown that exercised animals have beneficial effects on BV/TV compared with nonexercised animals. (71,84) A significant change in Tb.Th is an indication of loading-induced positive effects on normal bone-growing phenomena, (85) and the change in Tb.N is directly associated with the change in BV/TV and Tb.Th. (86) This explains why the MI group showed discontinued positive effects on Tb.N after 14 weeks of age, simultaneously with BV/TV and Tb.Th (Fig.…”
Section: Cyclic Loading Temporarily Reduced Body Weight and Food Intamentioning
confidence: 99%
“…Also, another study reported a greater BV/TV in the growing rat tibiae after 8-weeks of free fall exercise routine 70 . The observed increment in Tb.Th during the loading period is a part of normal bone development 71 . However, a significant increment in the loaded limbs (compared to shams) indicated an additional improvement in trabecular structure under impact loading conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As for Tb.Th, Tb.N, and Tb.Sp, no difference was found between the irradiated and control tibiae for the 0.83 Gy group ( Fig 6 ), while Tb.Th and Tb.N were significantly increased in the growing period for this group ( Table 2 ). The increment of Tb.Th during the growing period indicates normal bone growth process [ 24 , 60 , 61 ]. Moreover, the observed increase in Tb.N is associated with the concomitant increase in BV/TV for the young age period [ 62 ].…”
Section: Discussionmentioning
confidence: 99%